ANALISIS STRATEGI PENGELOLAAN OBJEK PARIWISATA GUNUNG KEMUKUS TAHUN 2022-2024 DI KABUPATEN SRAGEN - Istyana Ayu Wulandari; Dewi Erowati (Journal of Politic and Government Studies, 2026)
The management of tourism attractions is an important factor in increasing competitiveness between tourist attractions and influencing the sustainability of the tourism sector between regions. Mount Kemukus is one of the tourist attractions in Sragen Regency that has historical, cultural, and religious value. Mount Kemukus underwent revitalization since 2020 and was inaugurated in 2022. The revitalization was carried out on a large scale by creating new rides, facilities, and infrastructure, thereby creating a new look. The revitalization cost a considerable amount of money due to the overall changes, with a total budget of 48.4 million. This study was motivated by a problem related to the issue of suboptimal management. This problem arises from various factors, including limited land, budget, and low participation rates. These factors can be addressed by implementing an appropriate strategic plan. This management strategy plan is outlined in the agency's strategic plan with the aim of enhancing competitiveness and increasing visitor appeal. This study aims to provide an analysis of management strategies and also examine the supporting and inhibiting factors in the implementation of these strategies. The method used by the researcher is descriptive qualitative through interviews, observation, and documentation. Informants in this study include the head of tourism destination development, managers, local residents, business actors, and visitors. Data analysis was conducted through the stages of reduction, data presentation, and conclusion drawing. The theories used as a basis were strategic management theory and SWOT analysis. Through this study, researchers wanted to find out what strategies were used by the Sragen Regency Youth, Sports, and Tourism Office in managing the Mount Kemukus tourist attraction after its revitalization. Management requires cooperation between the management and the surrounding community. Therefore, it is necessary to strengthen the quality of human resources to create optimal human resources. The management of the Mount Kemukus tourist attraction is influenced by the quality of human resources who are not sufficiently aware. The researchers' findings show that the management of the Gunung Kemukus tourist attraction uses the agency's strategic plan for 2021-2026. The strategy covers four aspects, namely: development of tourism destination attractiveness, marketing of tourism destinations, development of the creative economy ecosystem, and development of tourism and creative economy resource capacity. From these four aspects, the researcher found that the first and second aspects are supporting factors, while the third and fourth aspects are inhibiting factors in management..